Hybrid education in the age of Education 5.0- A study of engagement and innovations in the Indian education system amidst covid-19 - Singh, Yuvika; Phoolka, Shivinder (Indian Journal of Educational Technology, 2025)
Amidst the global pandemic, the landscape of education witnessed a seismic shift, compelling both students and educators to embrace digital platforms for learning. Education 5.0 emerged as a beacon of hope, offering innovative solutions to navigate the challenges posed by the COVID-19 scenario. This paper presents an overview of the educational sector, focusing on the engagement and innovations that shaped hybrid education in the Indian Education System during the pandemic. Investigating the form and effectiveness of digital platforms, the research explores their benefits as vehicles for exchanging information. Additionally, it highlights the pivotal role of AI in Education 5.0, empowering educators with data-driven insights and personalized support through digital platforms. The study also explores the transformative potential of blended learning, envisioning a paradigm shift in India’s educational ecosystem through education 5.0- Faculty-student engagement model with the addition of Blended learning and Artificial Intelligence. Through this exploration of engaging pedagogies and cutting-edge technologies, the paper underlines the resilience of the Indian Education System amidst adversity.